2015
DOI: 10.1038/srep07561
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of weight loss via high fat vs. low fat alternate day fasting diets on free fatty acid profiles

Abstract: Cardiovascular disease risk is associated with excess body weight and elevated plasma free fatty acid (FFA) concentrations. This study examines how an alternate-day fasting (ADF) diet high (HF) or low (LF) in fat affects plasma FFA profiles in the context of weight loss, and changes in body composition and lipid profiles. After a 2-week weight maintenance period, 29 women (BMI 30–39.9 kg/m2) 25–65 years old were randomized to an 8-week ADF-HF (45% fat) diet or an ADF-LF (25% fat) diet with 25% energy intake on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
0
31
0
10
Order By: Relevance
“…In one study, ADF for 2 months resulted in decreases in resting heart rate, and circulating levels of glucose, insulin and homocysteine, all of which are favorable with regards to the risk of cardiovascular disease (Klempel et al, 2012). In another study, 2 months of ADF reduced fat mass, total cholesterol, LDL cholesterol and triglyceride concentrations (Varady et al, 2015). However, there have been few studies that have evaluated the relative effects of IF and CER on cardiovascular risk markers.…”
Section: If In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, ADF for 2 months resulted in decreases in resting heart rate, and circulating levels of glucose, insulin and homocysteine, all of which are favorable with regards to the risk of cardiovascular disease (Klempel et al, 2012). In another study, 2 months of ADF reduced fat mass, total cholesterol, LDL cholesterol and triglyceride concentrations (Varady et al, 2015). However, there have been few studies that have evaluated the relative effects of IF and CER on cardiovascular risk markers.…”
Section: If In Humansmentioning
confidence: 99%
“…Examples of specific IF diets include: complete fasting every other day (Bruce-Keller et al, 1999; Anson et al, 2003); 70% energy restriction every other day (Johnson et al, 2007; Varady et al, 2015); consuming only 500–700 cal two consecutive days/week (Harvie et al, 2011); and restricting food intake to a 6–8 h time period daily, which has also been termed ‘time restricted feeding’ (TRF) (Chaix et al, 2014). Examples of PF include a 4–5 day FMD (Brandhorst et al, 2015), 2–5 days of water only fasting (Raffaghello et al, 2008; Safdie et al, 2009), and 7 days of a FMD (Choi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…investigating CCR and 4 studying ICR. The 2 studies of ICR comparing low and high fat showed no difference between the groups [88,89] and similarly with CCR, Brinkworth et al [90] and Kirk et al [91] found no difference between a high fat, low carbohydrate diet and a low fat, high carbohydrate diet for weight, fat mass, fat-free mass or intra-abdominal fat and time to achieve 7% weight loss was the same. Nevertheless, Pascale et al [92] found that the addition of low fat to CR enhanced weight loss overall but when analysed into those with T2D and those without but with a family history of the condition, it appeared that the fat restriction only assisted weight loss in those with T2D and made no difference in those without.…”
Section: Continuous Caloric Restriction (Ccr) Versus Intermittent Calmentioning
confidence: 72%
“…Nevertheless, Pascale et al [92] found that the addition of low fat to CR enhanced weight loss overall but when analysed into those with T2D and those without but with a family history of the condition, it appeared that the fat restriction only assisted weight loss in those with T2D and made no difference in those without. To support this conclusion, the study by Brinkworth et al [90] and the 2 studies of ICR [88,89] which showed not difference, all compared high and low fat diets in subjects without T2D. In addition, Das et al [35] found that in young, overweight adults there was no difference in weight, percentage fat loss, fat-free mass or resting metabolic rate between 30% CR with a low glycaemic or a high glycaemic load.…”
Section: Continuous Caloric Restriction (Ccr) Versus Intermittent Calmentioning
confidence: 98%
“…IF means abstinence of food and drink in specified time periods. IF can be practiced in different forms, such as abstinence from food every other day (36), significant reduction in caloric consumption every other day (37), moderate caloric restriction for 2 consecutive days/week (38), restricting of food to specific times of a 24-r period, which is called TRF (21), abstinence from food for 1 or 2 days per week and then ad libitum food consumption for the rest of the week, as well as the diurnal IF performed by Muslims during the month of Ramadan where fasting performers abstain from food as well as drinks from dawn to sunset for the whole month (29-30 days) (39).…”
Section: Intermittent Fasting and Cardiometabolic Riskmentioning
confidence: 99%